Plasma-membrane Cnh1 Na+/H+ antiporter regulates potassium homeostasis in Candida albicans - Kinclová-Zimmermannová, Olga; Sychrová, Hana (Microbiology, 2007)
The physiological role of Candida albicans Cnh1, a member of the Na+/H+ antiporter family, was characterized. Though CaCnh1p had broad substrate specificity and mediated efflux of at least four alkali metal cations upon heterologous expression in Saccharomyces cerevisiae, its presence in C. albicans cells was important especially for potassium homeostasis. In C. albicans, CaCnh1p tagged with GFP was localized in the plasma membrane of cells growing as both yeasts and hyphae. Deletion of CNH1 alleles did not affect tolerance to NaCl, LiCl or CsCl, but resulted in increased sensitivity to high external concentrations of KCl and RbCl. The potassium and rubidium tolerance of a cnh1 homozygous mutant was fully restored by reintegration of CNH1 into the genome. The higher sensitivity of the cnh1/cnh1 mutant to external KCl was caused by a lower K+ efflux from these cells. Together, the functional characterization of the CaCnh1 antiporter in C. albicans revealed that this antiporter plays a significant role in C. albicans physiology. It ensures potassium and rubidium tolerance and participates in the regulation of intracellular potassium content of C. albicans cells.
Keywords: hyfy; chloridy; substrátová specifita; Candida albicans; cesium; Cloning, Molecular; Potassium Chloride; Drug Resistance, Fungal; testy genetické komplementace; buněčná membrána; chlorid lithný; antibakteriální látky; draslík; Financing, Organized; Lithium Chloride; Homeostasis; financování organizované; delece genu; chlorid sodný; Potassium; Saccharomyces cerevisiae; Fungal Proteins; Cell Membrane; rubidium; Gene Deletion; Yeasts; Cesium; fungální léková rezistence; Chlorides; Gene Expression; Substrate Specificity; Hyphae; Anti-Bacterial Agents; klonování DNA; fungální proteiny; chlorid draselný; kvasinky; Rubidium; Sodium Chloride; Genetic Complementation Test; Sodium-Hydrogen Exchangers; Na(+)-H(+) antiport; exprese genu; homeostáza